METAL COMPLEXES OF NICKEL, PALLADIUM AND PLATINUM WITH PYRAZOLYL PYRIDINE - Mahmud, Karamat; Khan, Misbahul Ain; lqbal, Muhammad Zafar (Biological Sciences - PJSIR, 2002)
The complexes of 2-(Pyrazol-l '-yl) pyridine with Ni (II), Pd(II) and Pt (II) are reported. Stability constants were carried out by Job's method of continuou s variation . The complexes were characterized on the basis of analytical data for metal determination by atomic absorption , elemental analysis, spectroscopic evidence and qualitative analysis by x ray diffraction. The ligand fonns a 1:1 complex with these metals.